Hot spots and frontiers of postpartum depression research in the past 5 years: A bibliometric analysis - Wang, Runfang; Shan, Yaokun (Frontiers in Psychology, 2022)
Objective: This study applied the bibliometric method to analyze the hotspots and frontiers in the field of postpartum depression research from 2017 to 2021. Methods: A computer-based search for studies related to postpartum depression (PPD) was conducted in the Web of Science Core Collection from 2017 to 2021. Using CiteSpace 5.8. R3 visualization software, this paper analyzed the hot spots and frontiers of postpartum depression research from countries, institutions, authors, cited references and keywords, and drew corresponding knowledge maps. Results: A total of 3,789 articles were retrieved, and the annual publication volume showed a steady increase.The countries and institutions with the most publications were the United States and the University of Toronto, respectively. Cindylee Dennis was the most productive author. The most frequently cited and centrally cited articles were meta-analyses on risk factors associated with antenatal depression or anxiety and meta-analyses on the prevalence of antenatal or postnatal anxiety, respectively. The research hotspots in the field of postpartum depression in the past five years mainly focused on the risk factors for PPD, and the impact of the COVID-19 epidemic on PPD. Providing various aspects of social and family support to women with PPD may be a research trend in this field. Conclusion: This study provides a trend and frontier in the field of postpartum depression, and valuable information for researchers to find potential partners and partner countries, and a reference for future research topics and development directions.